A Literature Review of Depression and Anxiety in Chronic Obstructive Pulmonary Disease (COPD) Patients - Umareta, Nurul Ramadhani (Scientia Psychiatrica, 2023)
Chronic obstructive pulmonary disease (COPD) is a disease that causes disability problems in the world. The high incidence exacerbation of COPD causes an increase in hospitalization rates. Depression and anxiety are conditions that are often associated with COPD, this is due to the burden of disease borne on patients such as shortness of breath, intensity of recurrence, chest pain, chronic cough with productive sputum that interferes with the quality of daily life patients. To assess the scale of depression and anxiety in COPD patients, the Hamilton Depression Rating Scale (HAMA) is used to determine the anxiety scale and the Hamilton Depression Rating Scale (HAMD) is used to assess the depression scale in COPD patients. Both of these scales are tools that are often used in the world because they have good consistency and validity. This literature review also discusses the effective therapies for depression and anxiety patients in COPD such as pulmonary rehabilitation, oxygen therapy, and also includes psychological pharmaceutical therapy.